Using Mind Maps to Improve 4th Graders’ Oral Performance in “Speak Out” Lessons: Action Research at a Primary School in Hanoi - Huong, Ta Thi Thanh (VNU Journal of Science: Education Research, 2024)
This research delves into the application of mind maps during speaking lessons, specifically focusing on their impact on enhancing oral performance in primary school students. The study aims to evaluate the effectiveness of mind maps in this context and measure the satisfaction levels of the students. Data collection involved pre and post-tests, along with a set of questionnaire administered after the intervention. The research included 29 fourth-grade students, with an 11-lesson treatment duration, each lasting 45 minutes. Results indicated significant improvement in students' speaking outcomes following the intervention, and participants expressed satisfaction with the help of mind maps in their lessons. The paper concludes by suggesting pedagogical implications and recommending further studies, with the goal of providing valuable insights for English teachers, educators, and students to optimize the use of mind maps in speaking lessons.